THE IMPACT OF WORK MOTIVATION, WORK ENVIRONMENT, AND CAREER DEVELOPMENT ON EMPLOYEE JOB SATISFACTION - Ahmad Prayudi; Imas Komariyah (Jurnal Visi Manajemen, 2023)
Human resources are very important in a company. therefore every company always tries to have quality human resources and companies must pay attention to aspects of work related to human resources, because without quality human resources a company will not run well between HR and companies must have a mutually beneficial relationship requires, companies need quality employees, employees also need a work environment that can provide satisfaction such as having a clean and comfortable work environment, one of the company's activities to advance the abilities of its employees is employee career development and providing motivation to employees from research is to determine the effect of motivation , work environment and career development on job satisfaction of employees of PT. Kalibaru Indonesia This research is included in the category of quantitative research. The total population is 302 employees, so the sample used is 77 employees because it uses the Slovin formula. From these results work motivation, work environment and career development affect job satisfaction.